The SLMTA programme: Transforming the laboratory landscape in developing countries - Katy Yao; Talkmore Maruta; Elizabeth T. Luman; John N. Nkengasong (African Journal of Laboratory Medicine, 2014)
Background: Efficient and reliable laboratory services are essential to effective and well-functioning health systems. Laboratory managers play a critical role in ensuring the quality and timeliness of these services. However, few laboratory management programmes focus on the competencies required for the daily operations of a laboratory in resource-limited settings. This report provides a detailed description of an innovative laboratory management training tool called Strengthening Laboratory Management Toward Accreditation (SLMTA) and highlights some challenges, achievements and lessons learned during the first five years of implementation (2009–2013) in developing countries.